Beyond the Sacred “Peralihan” Ritual: Local Beliefs and Spiritual Negotiations in Malay-Islamic Culture - Rina Rehayati; M. Ridwan Hasbi; Martius Martius (UIN Sunan Kalijaga Yogyakarta, 2025)
This study challenges dominant perspectives that reduce Malay Muslim rites of passage to either residual traditions or fully Islamized practices. Focusing on communities in Siak and Palembang, it conceptualizes ritual as a dynamic arena of negotiation, where Islamic norms and local symbols are continuously reinterpreted rather than simply preserved or purified. Using ethnographic methods, the study demonstrates that practices such as tepung tawar, mandi limau, and doa selamat persist through processes of re-signification. Meanings once associated with magical protection are reframed within a tawhidic logic that shifts efficacy from objects to divine intention. This transformation is not merely theological but also social, as it redistributes authority among religious leaders, customary elites, and participants, producing a negotiated and embodied religiosity. The findings argue that Islamization operates not as a top-down imposition but as a dialogical process in which communities actively recalibrate the boundaries of the sacred. Ritual thus functions as a mediating mechanism that sustains cultural continuity, reinforces social cohesion, and secures religious legitimacy. By foregrounding this process, the study advances the concept of cultural piety, demonstrating that Malay Muslim religiosity is shaped through ongoing negotiation, where meaning remains fluid yet socially grounded.